Pengaruh Corporate Social Responsibility (CSR), Green Accounting, Keragaman Gender, dan Keragaman Usia Terhadap Kinerja Keuangan - Firda Khalimatussyadiyah; Dirvi Surya Abbas; Imam Hidayat (Politeknik Ganesha Medan, 2025)
This study examines the relationship between Corporate Social Responsibility (CSR), Green Accounting, Gender diversity of the Board of Directors, and diversity of the board of directors' age on financial performance. Using purposive sampling, 220 manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2019-2023 were selected as research samples based on the availability of annual and reports. This study uses data panel regression analysis to test the relationship between variables and uses the Eviews 12 test to test the effect of financial performance between independent and dependent variables. The results of the study indicate that Corporate Social Responsibility (CSR) has a positive effect on financial performance. Green Accounting has a positive effect on financial performance. The board of directors' gender diversity has no effect on financial performance. The board of directors' age diversity has a positive and insignificant effect on financial performance. This study still has limitations in the independent variables used, only a few variables, so that in further research it is better to add other independent variables that have not been used in this study so that the results of further research get better research results.